MEANS OF STIMULATING THE DEVELOPMENT OF SMALL BUSINESS AS A FACTOR OF OVERCOMING THE DEPRESSION OF REMOTE SETTLEMENTS OF TERRITORIAL COMMUNITIES - AVHUSTYN, Ruslan; DEMKIV, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The study revealed the relevance of the issues of policy formation of balanced spatial development of territorial communities, in particular in terms of overcoming the depression of remote settlements with the use of such a tool as small business development, stimulating the growth of business activity of the population, employment and self-employment. The purpose of the study is to identify promising and effective means of stimulating the development of small entrepreneurship in the projection of overcoming depression in remote settlements of territorial communities. An effective factor in overcoming the depression of remote areas and at the same time ensuring the leveling of disparities in local economic development is the activation of small businesses in these areas. The policy of local authorities in this direction should be implemented in the following directions: improving access to financial and investment resources, attracting intellectual and human resources, strengthening the material and technical support of small enterprises, improving the integration of small enterprises into the local economic system, developing business skills, consulting and informational support. According to these vectors, it is expedient to plan and implement the relevant instruments of local economic policy. It is important that they relate to the formation of specialized financial and credit programs; creation of financial and credit support funds; attraction of migrant workers’ funds; budget and grant support; attraction of financial resources of international technical assistance, stimulation of business entities for personnel training; use of the state order for teaching activities and training of personnel in the countryside, creation and development of local integrated systems, clusters with the participation of large and small enterprises, creation and development of local integrated systems, clusters with the participation of large and small enterprises; support for franchising programs of manufacturers for the development of the production complex of rural areas, creation of business incubators and business support centers; providing certificates to small business entities for consulting and other business services; development of business infrastructure in remote areas.